Case Report: A complex case of an adolescent female with comorbid borderline personality disorder and autism spectrum disorder - Močnik, Sara; Gregorič Kumperščak, Hojka; Demšar, Ajda (Frontiers in Psychiatry, 2025)
Diagnosing borderline personality disorder (BPD) and autism spectrum disorder (ASD) in adolescent females presents significant challenges due to the overlap in their symptomatology. Both conditions share features such as emotional dysregulation, impulsivity, and difficulties in interpersonal relationships, making differentiation crucial yet difficult. This case report examines an adolescent female with co-occurring BPD and ASD, emphasizing the complexities of distinguishing between the two. It explores the role of developmental history, behavioral patterns, and neurobiological factors in forming a precise diagnosis. Additionally, the report highlights the impact of comorbid conditions like depression and anxiety, which frequently accompany both BPD and ASD, further complicating the diagnostic process. By focusing on this case, we underscore the importance of a thorough, multidimensional diagnostic approach to ensure accurate identification and treatment. The case serves as a reminder of the need for heightened awareness of how BPD and ASD can present in females and advocates for more nuanced diagnostic tools and tailored interventions to improve clinical outcomes for this population.